Morphology of the cisterna chyli in nine dogs with idiopathic chylothorax and in six healthy dogs assessed by computed tomographic lymphangiography. Issue 1 (11th November 2020) - Rengert, Roger; Wilkinson, Tom; Singh, Ameet; Brisson, Brigitte A.; Fransson, Boel
Abstract: Objective: To describe the morphology of the lymphatics in the region of the cisterna chyli in healthy dogs and in dogs with idiopathic chylothorax by using computed tomographic lymphangiography. Study Design: Retrospective study. Animals: Nine dogs with idiopathic chylothorax and six healthy dogs. Methods: Computed tomographic lymphangiograms were reviewed to evaluate the number of cisterna chyli branches, total cross‐sectional area of the branches normalized to the cross‐sectional area of the aorta, number of branches with cross‐sectional area greater than 25% of the aorta cross‐sectional area, and ratio of the total perimeter to the total cross‐sectional area of the branches. Data (mean ± SD) were compared between unaffected dogs and dogs with idiopathic chylothorax. Results: The cisterna chyli included more branches in dogs with chylothorax (4.30 ± 1.57) than in unaffected dogs (1.67 ± 0.56, P = .02), occupying a relative perimeter approximately double that in unaffected dogs ( P  < .001). The relative cross‐sectional area of the cisterna chyli was approximately twofold smaller in affected (0.73 ± 0.35) than in unaffected (1.63 ± 0.91, P = .02) dogs. The fraction of dogs with branches greater than 25% of the cross‐sectional area of the aorta tended to be larger in unaffected dogs ( P = .07). Most larger branches were located dorsal or to the right of the aorta. Conclusion: The cisterna chyli of dogs with idiopathic chylothorax contained smaller and more numerous branches compared with that of unaffected dogs. Clinical significance: Altered cisterna chyli morphology may impact the surgical approach for cisterna chyli ablation in dogs with idiopathic chylothorax.